Enhancing the performance of pure organic room-temperature phosphorescent luminophores - Kenry (Nature Portfolio, 2019)
Pure organic molecules displaying room-temperature phosphorescence (RTP) are a rapidly emerging class of luminophores. In this Review, the authors discuss the principles for their rational design and development, from the underlying photophysical mechanisms of organic RTP, to enhancement and processing strategies for their practical application.